2023
DOI: 10.1103/physrevd.107.023010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of updated multipole Love numbers and f -Love universal relations in the context of binary neutron stars

Abstract: Neutron star (NS) equation of state (EoS) insensitive relations or universal relations (UR) involving neutron star bulk properties play a crucial role in gravitational-wave astronomy. Considering a wide range of equations of state originating from (i) phenomenological relativistic mean field models, (ii) realistic EoS models based on different physical motivations, and (iii) polytropic EoSs described by spectral decomposition method, we update the EoS-insensitive relations involving NS tidal deformability (Mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…We also assume a power-law prior for luminosity distance ( ) d L 2 and isotropic prior for inclination angle. For the additional parameters, such as Λ 3 , Σ 2 , and ω 2 , we use the universal relations from Pradhan et al (2023c). The remaining BNS parameters (such as sky position) are kept fixed at their injected values to reduce the computational cost.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also assume a power-law prior for luminosity distance ( ) d L 2 and isotropic prior for inclination angle. For the additional parameters, such as Λ 3 , Σ 2 , and ω 2 , we use the universal relations from Pradhan et al (2023c). The remaining BNS parameters (such as sky position) are kept fixed at their injected values to reduce the computational cost.…”
Section: Methodsmentioning
confidence: 99%
“…Several investigations have been conducted to determine the impact of the dynamical tidal correction for the event GW170817 (Pratten et al 2020;Gamba & Bernuzzi 2023;Pradhan et al 2023c). Even though there is no statistically significant support (based on the Bayes factor comparison) for the inclusion of dynamical tidal corrections over adiabatic tides for the GW170817, the bias on the recovered tidal parameters cannot be disregarded (Gamba & Bernuzzi 2023;Pradhan et al 2023c). This can be explained by looking at the relatively low sensitivity of the GW detector in the region where the Note.…”
Section: Gw170817mentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the neutron star radius can also be inferred using the tidal deformability of the neutron star, which can be measured precisely by Cosmic Explorer during the inspiral. We convert measurements of deformability Λ 2 to compactness  using the universal relations between the quadrupolar dimensionless tidal deformability and the neutron star compactness (e.g., Maselli et al 2013;Godzieba et al 2021;Keshari Pradhan et al 2022). The latter two studies fit a sixth-order polynomial for the …”
Section: Analysis Of a Simulated Nsbh Signalmentioning
confidence: 99%
“…The URs have been studied in subsequent works with different assumed NS EOS models or different NS compositions (Benhar et al 2004;Sotani et al 2011;Flores et al 2017;Ranea-Sandoval et al 2018;Das et al 2021;Jaiswal & Chatterjee 2021;Pradhan & Chatterjee 2021;Aguirre 2022;Pradhan et al 2022;Ranea-Sandoval et al 2022;Zhao & Lattimer 2022;Kumar et al 2023). Though initial URs involved the compactness (M/R) and mean density of the star, later works have shown that there exists universality of mode parameters with the inertia parameter (Lau et al 2010;Chirenti et al 2015), the tidal deformability parameters (Chen & Piekarewicz 2014;Pradhan et al 2023b), and with the nuclear parameters (Sotani 2021;Kunjipurayil et al 2022), which are helpful in different scenarios in the NS asteroseismology problem. Additionally, significant effort has been put forward to investigate the impact of rotation on the QNMs and the NS asteroseismology or URs (Kastaun et al 2010;Zink et al 2010;Gaertig & Kokkotas 2011;Yoshida 2012;Doneva et al 2013;Passamonti et al 2013;Pnigouras & Kokkotas 2016;Yazadjiev et al 2017;Rosofsky et al 2019;Krüger & Kokkotas 2020a, 2020b.…”
Section: Introductionmentioning
confidence: 99%